2021
DOI: 10.3390/antiox10071067
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antioxidant Supplementation on Operated or Non-Operated Varicocele-Associated Infertility: A Systematic Review and Meta-Analysis

Abstract: In patients with varicocele-associated infertility, the effect of antioxidant supplementation on fertility is unknown. We performed a systematic review and meta-analysis to explore their role in patients with operated or non-operated varicocele. We searched major databases and sources of grey literature until May 2021 (PROSPERO: CRD42021248195). We included 14 studies (980 individuals) in the systematic review. Of the 14 studies, 2 explored the effect of antioxidant supplementation in patients with non-operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Because of its potent antioxidant effects, this vitamin is particularly useful for protecting sperm DNA from damage caused by ROS [209]. Vitamin C levels are low, and reactive oxygen species (ROS) levels are high in the seminal plasma of males who have asthenozoospermia [210,211]. On the other hand, the level of vitamin C and sperm motility are related to one another in a manner that is depending on the dose.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…Because of its potent antioxidant effects, this vitamin is particularly useful for protecting sperm DNA from damage caused by ROS [209]. Vitamin C levels are low, and reactive oxygen species (ROS) levels are high in the seminal plasma of males who have asthenozoospermia [210,211]. On the other hand, the level of vitamin C and sperm motility are related to one another in a manner that is depending on the dose.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…As far as pregnancy rates are concerned, no significant differences were demonstrated after antioxidant treatment versus no treatment at three (OR: 2.28, 95% CI: 0.7-7.48) and six months (OR: 1.88, 95% CI: 0.62-5.72) in patients who underwent varicocele surgical repair. Given the controversial finding for sperm concentration, morphology, motility, and DNA fragmentation, no definite conclusions regarding the optimal type, dosage, and treatment duration could be safely drawn [83].…”
Section: Antioxidant Treatment For Male Infertility-friend or Foe?mentioning
confidence: 99%
“…One of the suggested treatments is the use of antioxidant supplementation to neutralize the oxidative stress caused by the activated inflammatory pathways. However, in addition to the existence of contradictory literature, the authors of a recent was concluded that this approach does not seem to improve either seminal parameters or pregnancy rates [7]. More effective results seem to be obtained when varicocele is treated by surgical varicocelectomy [6].…”
Section: Introductionmentioning
confidence: 99%